Fields of bounty [large type] - Snelling, Lauraine; Giron, Kiersti (Snelling, Lauraine. Leah's garden, 2023)
"Lilac Nielsen's dream has come true: handsome young Rev. Ethan Pritchard has finally noticed her. Yet she must balance this new courtship with the pursuit of another dream--the publication of her artwork in a New York paper. She has secretly been submitting a series of drawings under a pen name, and if anyone traces the drawings back to her, the entire Nielsen family could be put in danger.As their family farm expands and Lilac's relationship with the reverend grows, it's a time of new beginnings. But when a family crisis back in Ohio shakes the Nielsen sisters, can they continue to build the new life they've begun in Nebraska? And will Lilac be prepared for what God has in store for her future?Bestselling author Lauraine Snelling invites you back to Salton, Nebraska, where friendship and romance blossom"--